Pressure-induced K–Λ crossing in monolayer WSe2. Issue 20 (11th May 2016) - Ye, Yanxia; Dou, Xiuming; Ding, Kun; Jiang, Desheng; Yang, Fuhua; Sun, Baoquan
Abstract : The energy band structures and related room temperature exciton transitions of monolayer and bilayer tungsten diselenide (WSe2 ) are investigated using photoluminescence (PL) spectra under hydrostatic pressure up to 5.42 GPa. Abstract : The energy band structures and related room temperature exciton transitions of monolayer and bilayer tungsten diselenide (WSe2 ) are investigated using photoluminescence (PL) spectra under hydrostatic pressure up to 5.42 GPa. For monolayer WSe2, it is found that the conduction band Λ valley is 70 ± 30 meV higher than the K valley at zero pressure, and the K – Λ valley crossover happens at a pressure of approximately 2.25 GPa. The PL peak of exciton related to the direct K – K interband transition in monolayer and bilayer WSe2 shows a pressure-induced blue-shift at the rates of 31.5 ± 0.6 and 27 ± 1 meV GPa −1, respectively. The indirect Λ – K interband transition for monolayer and bilayer WSe2 exhibits a distinctly different pressure response. The pressure coefficient is as small as −3 ± 6 meV GPa −1 for monolayer, but a much larger value of −22 ± 1 meV GPa −1 for bilayer WSe2, indicating that the interlayer coupling has a strong effect on the electronic states at the Λ valley.